Process of Preparing 3-methyl-6-nitro-1H-indazole by Scale of 180 g/batch as an Important Intermediate for the Preparation of Pazopanib - Thi Thanh Cham, Bui; Quoc Hung, Phan; Tra Ly, Tran; Thi Ngoc, Nguyen; Thi Luyen, Bui; Thu Quynh, Nguyen; Nguyet Suong Huyen, Dao; Dinh Luyen, Nguyen; Van Giang, Nguyen; Van Hai, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2023)
Pazopanib hydrochloride, marketed worldwide under the brand name Votrient, is an anti-cancer medication manufactured by Novartis. It is the first and only tyrosine kinase inhibitor currently approved for the treatment of multiple histological subtypes of soft tissue sarcoma (STS). In previous studies, we presented initial results regarding the synthesis of 3-methyl-6-nitro-1 H -indazole ( 3 ) as an important indazole component on a laboratory scale (approximately 10 g/batch). In this study, we have successfully synthesized this compound ( 3 ) at a scale of 180 g/batch, achieving an overall process yield of 79.6 % from the starting material 2-ethylaniline. This yield is higher than that reported in previous publications. Some of the technical conditions that have been improved include optimizing the amount of sulfuric acid in the nitration reaction, the amount of acetic acid and sodium hydroxide in the diazotization reaction for ring closure, reaction temperature, and the feed method to control the reaction safely and achieve high efficiency at a scale of 180 g/batch. Keywords: I ndazole, scale-up, synthesis, pazopanib.